Neurobiological mechanisms of the effect of exercise on depressive disorder: analysis using CiteSpace - Yang, Haiying; Xu, Jiayi; Hou, Lei; Huang, Dejian (Frontiers in Psychiatry, 2025)
Research on the neural mechanisms of exercise interventions for depressive disorder has evolved significantly over the past decade; however, there remains a lack of scientometric synthesis tracking these changes, including analyses of researcher networks and scientific productivity up to December 31, 2024. We searched the Web of Science Core Collection using specific search terms and conducted a comprehensive scientometric analysis to systematically examine the evolutionary pathways, collaborative networks, and core mechanisms in the relevant literature from 2006 to 2024. Our analysis included 170 core studies, and the co-cited reference network identified seven clusters with well-structured networks (Q=0.9299) and highly confident clustering (S=0.9794). Results revealed that exercise exerts antidepressant effects through modulation of neurotransmitter systems (e.g., 5-HT, GABA receptor subtypes), up-regulation of brain-derived neurotrophic factor (BDNF) expression, and enhancement of hippocampal neuroplasticity. The research development was divided into three distinct phases: the early phase (2006-2014), which validated the effects of exercise on monoamine transmitters; the middle phase (2015–2019), which confirmed that aerobic exercise can produce effects comparable to pharmaceutical interventions; and the recent phase (post-2020), which has focused on gene-environment interactions and metabolism-neuraxis mechanisms. The collaborative network has expanded from the initial Swiss-German axis to a global level. Future research should integrate metabolomics and neuroimaging technologies to develop precise exercise prescriptions and optimize real-time intervention feedback using digital tools, thereby providing theoretical frameworks and translational pathways to enhance non-pharmaceutical intervention strategies.